Forest Fires and their Effects on Rural Algerian Society between 1860 and 1881. The Region of Jemmapes (Azzaba) as a Model - ibn achene, Khalid Abdennour; Meddour, Khamissa (Jordan Journal for History and Archaeology, 2025)
Comprehending the importance of the forestry sector in Algeria at the onset of colonization, the French colonial administration undertook its organization and control, particularly after the intense series of forest fires that affected the forested region. This was notable in the mixed municipality of Jemmapes during the period 1860-1892, causing significant losses that greatly impacted the French administration and the primary Algerian pastoral tribes that heavily relied on forest resources for their daily activities. The objective of this research paper is to identify the series of forest fires in the mixed municipality of "Jemmapes" by studying their main causes and their effects on the local population. The aim is to uncover the policy of the French colonial administration in dealing with the issue of forest fires in Algeria, using the municipality of “Jemmapes” as a model. This will be accomplished through the examination of available archival source material and publications from the General Government in Algeria.